Increasing Student Learning Outcomes in Science Learning Through Image Media Students Of Class V SD Negeri 01 Gondosuli in Academic Year 2021/2022 - Kristanti, Wening (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The low student learning outcomes in science lessons are caused by inappropriate learning media. The aim of this research is to improve student learning outcomes in the natural sciences learning content through the media of images in fifth grade students at SD N 01 Gondosuli in the 2020/2021 academic year. This research was conducted in 2 cycles. The research subjects are teachers and students. Data collection techniques used are observation and tests. The results showed that there was an increase in student understanding, teacher skills and student abilities. Student activity in science learning using media images cycle I with sufficient criteria, increased in cycle II with good criteria. Mastery learning in cycle I, from learning outcomes 62.5%, namely 2 out of 7 students with an average score of 74, while in cycle II mastery increased to 100% or 7 out of 7 students with an average score of 85.